Alley coppice-a new system with ancient roots - Morhart, Christopher D.; Douglas, Gerry C.; Dupraz, Christian; Graves, Anil; Nahm, Michael; Paris, Pierluigi; Sauter, Udo H.; Sheppard, Jonathan; Spiecker, Heinrich (EDP Sciences, 2014)
Context: Current production from natural forests will not satisfy future world demand for timber and fuel wood, and new land management options are required. Aims: We explore an innovative production system that combines the production of short rotation coppice in wide alleys with the production of high-value trees on narrow strips of land; it is an alternative form of alley cropping which we propose to call 'alley coppice'. The aim is to describe this alley coppice system and to illustrate its potential for producing two diverse products, namely high-value timber and energy wood on the same land unit. Methods: Based on a comprehensive literature review, we compare the advantages and disadvantages of the alley coppice system and contrast the features with well-known existing or past systems of biomass and wood production. Results: We describe and discuss the basic aspects of alley coppice, its design and dynamics, the processes of competition and facilitation, issues of ecology, and areas that are open for future research. Conclusion: Based on existing knowledge, a solid foundation for the implementation of alley coppice on suitable land is presented, and the high potential of this system could be shown.